Role of Job Satisfaction of Teachers in Emerging Education Scenario: Understanding the evolving challenges in the teaching profession (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education is a constructive and life long process which drags a child from illiteracy, darkness, poverty and misery and leads him to the pool of growth, prosperity and happiness by developing his her personality in all respects i.e. physical, mental, social, emotional spiritual. It is a lifelong process that starts from at birth of the child and continues till death. An educational institution is a miniature of the society as it has students of all caste, race, religion and gender. It means by serving students, a teacher is also serving a society and a nation too. Swami Vivekananda had emphasised that to give the best to students is the utmost responsibility of a teacher. It is the prime responsibility of a teacher to inculcate the students in such a manner that after delivering the content the teacher must have the feeling of Satisfaction. A teacher who is satisfied with hisher job can give hisher best to his students. Teachers with high level of Job Satisfaction can achieve their goals i.e. they are able to bring desirable changes in in students behaviour and their outcomes. Teachers who have high levels of job satisfaction can motivate their students to achieve the goals. In olden days teaching profession was considered as one of the most comfortable job with high level of Job Satisfaction. Now gone are those days, as teaching profession has become very challenging gradually. In present education scenario only those teachers can survive who have the ability to draw satisfaction from their job.